The Concept of Islamization of Science from the Perspectives of Al-Faruqi and Al-Attas - Ridwan, Mohammad; Saputra, Edy; Hamdanil; Daulay, Irmasani; Effendi, Amri; Danil, Muhammad (The Future of Education Journal, 2024)
The science that is circulating today has been influenced by Western philosophy, namely secularism and skepticism. This has led to the separation of religion (God) from science, with doubt becoming the foundation in the search for truth. This is, of course, in contrast to Islamic values. Therefore, Ismail Raji Al-Faruqi and Syed Muhammad Naquib Al-Attas offer the concept of the Islamization of science as a solution to the problems faced. The aim of this research is to examine the concept of the Islamization of science according to Ismail Raji Al-Faruqi and Syed Muhammad Naquib Al-Attas and its implications for the development of Islamic education. In this research practice, the researcher uses a qualitative approach and a descriptive method of non-interactive study. Data collection was carried out through literature study techniques, with the researcher as the key instrument. The collected data was then analyzed through the stages of data reduction, data display, and conclusion drawing. The results of this study show that there are both similarities and differences regarding several concepts within the Islamization of science in the views of Al-Faruqi and Al-Attas. Among the similarities is the background that justifies the need for Islamization. The differences between them are found in the stages of the Islamization of science. Al-Attas provides a general explanation with two stages: alienation and absorption. In contrast, Al-Faruqi offers a detailed explanation of this process with 12 stages. Another finding from this research indicates that the concept of the Islamization of science has implications for the development of Islamic education, covering institutional, curriculum, and educator aspects.